Movement material - Rasmus Ölme (Cappelen Damm Akademisk NOASP, 2017)
How can a materialist approach contribute to the development of contemporary dance and choreography? That is the question that this article aims to investigate through the formulation of the current status of the ongoing artistic research project Movement Material. The project relates to topics within the philosophy of materialism, but focuses on practical artistic research. The article delineates the knowledge production that may emerge from the exploration of a materialist approach to dancing, understood as an attunement between sensory and cognitive capacities. These two capacities are understood as relational and transposed into the practice through two terms, dance and choreography.